Genetic parameters for wood quality, growth and branching traits in Pinus patula - Escobar-Sandoval, Margarita Concepción; Vargas-Hernández, J. Jesús; López-Upton, Javier; Espinosa-Zaragoza, Saúl; Borja-de la Rosa, Amparo (Instituto de Ecología, A.C., 2018)
Determining genetic parameters for economically important traits related with productivity and wood quality is required to establish the most appropriate breeding strategy in forest trees. In this study, the heritability and genetic and phenotypic correlations of traits related with wood quality (basic wood density and tracheid length), growth (total stem height, diameter and volume) and branching (branch number, diameter and angle, and number of whorls) were estimated in eight-years-old, open-pollinated progenies of Pinus patula. A broad genetic variation was found for most traits, but genetic control was low to moderate in them (≤ 0.10 h2i ≤ 0.25), except for tracheid length and branch number, which did not show significant (P > 0.05) genetic variation. The correlation structure showed a favorable relationship for most traits, with genetic correlations between -0.23 and 0.98 and phenotypic correlations between 0.02 and 0.93. Results suggest that it is possible to use some of these traits as selection criteria either independently or combined to increase growth and wood quality without causing negative collateral effects on the other economically important traits.